PROPUESTA DE SENDERIZACIÓN Y SEÑALIZACIÓN EN EL BOSQUE PROTECTOR EL SAYO DE LA PARROQUIA RURAL SANTIAGO DEL CANTÓN LOJA Y PROVINCIA DE LOJA - Bustamante Cabrera, Marlon Paúl (2016)
Protected areas have been recognized as the main strategy for the conservation of biodiversity. At the same time, these areas contribute to human welfare, since they help to conserve natural resources and maintain ecosystem services that support life of millions of people. Management categories of the National System of Protected Areas are large areas, because of the fragility of ecosystems and their economic and social importance, care measures and coordination of structural nature are taken at national level to achieve conservation objectives and sustainable development. All these features make the Ecuador and mainly in the province of Loja, a tourist destination with great potential to develop nature tourism and adventure South of Ecuador, in the Sierra region is the Rural Parish Santiago Canton Loja belonging to the province of the same name; Santiago has important potential resource to be exploited for tourism This draft "PROPOSAL SENDERIZACIÓN AND SIGNING OF FOREST COVER THE SAYO PARISH RURAL SANTIAGO, Loja Canton, Loja province" is an initiative considered in order to contribute to the progress and development of tourism in the place aforementioned . The general objective of this project was determined "Develop the proposed signage Senderización and protective forest Sayo rural parish Santiago Canton province of Loja and Loja" For three specific objectives focused development were raised: Analyze the current situation where the protector is Sayo Forest; Senderización make the proposal and signage for the protective forest Sayo; Develop a tour guide for the protective forest Sayo; results and socialize with the community involved. For the consequent development of the objectives it was necessary to apply methods and techniques, and for the first objective the direct observation technique was used, as an array of tourist diagnosis of Carla Ricaurte Quijano was developed adjusting to the reality of the parish study also profiles the strategic sites in the forest guard the Sayo was performed to obtain specific data like, category, type, subtype, location, and characteristics of each of the existing natural attractions in the place finally SWOT analysis technique was implemented This result allowed to establish tourism development strategies that will benefit the parish. For the second objective the development of analytical and scientific method that helped me to detail the technical descriptions for making signs, for which the creation of eight totems of information in different parts of the proposed route was used. The same interview technique that was applied 5 to the chairman of the parish of Santiago GAD to analyze the current situation of the Bosque Protector Sayo was also used. Also the physical load capacity, real and effective was determined to obtain the results of visits to the forest. Finally to realize the third objective scientific method was used, research techniques and data collection for the preparation of the guide path, which state more relevant Protected Forest information Sayo also applied subsequently results socialized developing the project with the parish president Santiago where I emphasize the importance of this proposal to increase tourism and above all protect the environment. It is concluded that the Bosque Protector Sayo Forest is a natural fit for birdwatching ecotourism hiking trails and the type of construction of the signage it is adequate to the study area, based on tourism signage manual prepared by the Ministry of Tourism of Ecuador. Therefore recommendations were made to the inhabitants of the rural parish Santiago exploit natural resources also have to the authorities of GAD Parish of Santiago, perform due this attractive promotion, training people in tourism that benefit this awareness activity and the care and maintenance of these natural areas.